2021
DOI: 10.1111/jgh.15504
|View full text |Cite
|
Sign up to set email alerts
|

Systemic quinolones and risk of acute liver failure III: A nested case–control study using a US electronic health records database

Abstract: Background and Aim: Quinolones are globally popular antibiotics with proven potency, broad coverage, and reasonable safety. However, some concerns were raised as to their possible association with acute liver failure (ALF). The aim of this study is to assess ALF risk within 30 days of receiving a systemically administered quinolone antibiotic, in individuals with no history of liver/diseases. Methods: We conducted a nested case-control study using electronic health records from the Cerner Health Facts. The ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In a companion study of real‐world electronic health records, ciprofloxacin showed evidence of a possibly increased AHF risk in persons with low comorbidity 49 . No other quinolones showed a significant signal, despite showing up in some AHF reports.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a companion study of real‐world electronic health records, ciprofloxacin showed evidence of a possibly increased AHF risk in persons with low comorbidity 49 . No other quinolones showed a significant signal, despite showing up in some AHF reports.…”
Section: Discussionmentioning
confidence: 98%
“…As such, significant evidence of disproportionate reporting is primarily thought to be hypothesis generating, requiring confirmation using other data sources. This has been done in our companion paper, which investigated the association of quinolones with AHF in a large EHR database for reference 49.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first part provides summary of evidence based on data mining of reports recorded in the US FDA Adverse Event Reporting System (FAERS) [36]. The third part involves a case-control study based on a major US electronic health records database [37].…”
Section: Search Methods For Identification Of Studiesmentioning
confidence: 99%
“…Despite the development of adverse events, emergence of resistance, and the availability of other treatment alternatives [2], this favored status persisted. Whereas many researchers consider nested case-control study based on a major US electronic health records database that includes detailed medical and sociodemographic information on more than 70 million patients from 500 different hospitals across the US between 2000-2016 [43].…”
Section: Introductionmentioning
confidence: 99%